AFATINIB-A COMPREHENSIVE REVIEW OF ANALYTICAL METHODS DEVELOPED IN PHARMACEUTICALS AND BIOLOGICAL MATRICES - KUMAR, HEMANTH; KUMAR, LALIT; VERMA, RUCHI (International Journal of Applied Pharmaceutics, 2024)
Afatinib is a selective irreversible ErbB family blocker that can be taken orally and has demonstrated broad-range effectiveness in preclinical studies against Epidermal Growth Factor Receptor (EGFR) mutations. The inhibition of ErbB receptors by afatinib may stop the development and spread of tumours because they are crucial for cellular proliferation and apoptosis. A modulator of the tyrosine kinase receptor known as afatinib treats specific types of metastatic non-small cell lung cancer. Afatinib has been found to produce acute liver injury, also apparent rare cases of death, and is associated with momentary elevations in serum aminotransferase levels at the time of therapy. The analytical techniques for evaluating afatinib in pharmaceuticals and biological matrices are the main subject of this study. For each method, the important validation parameters such as linearity, detection system, retention time, mobile phase, limit of Detection (LOD), and limit of Quantification (LOQ) are examined. Additionally, the discussion includes important quality characteristics like sensitivity, specificity and technique utilised for sample preparation pertaining to bioanalytical methods.